2018
DOI: 10.1016/j.jesf.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in older adults: Benefits from the productive engagement in physical activity

Abstract: Background/objectiveProductive engagement can be a strategy to reduce stress and chaos. Physical activity, a basic type of productive activity, could benefit older adults. Therefore, the purpose of this study was to explore how productive engagement in physical activity may influence older adults in maintaining their health-related quality of life when they live in a long-term care facility.MethodsWe used purposive sampling to recruit 163 participants from 14 long-term care facilities in Taiwan. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 24 publications
3
36
0
2
Order By: Relevance
“…Yen and Lin introduced physical activity to older adults in a long-term care facility in Taiwan, showing significant QOL benefits. 107 Lavie and Milani compared older adults ≥70 years of age to younger patients <55 years in CR, finding those ≥70 years had significant improvement in QOL scores, even greater than in younger patients (20% vs 15%, P = .03). 108 Another study by Lavie and Milani showed QOL, pain, energy, physical function, well-being, general health, and mental health scores all significantly improved in cardiac patients who participated in CR, with similar benefits in patients ≥65 years and younger cohorts.…”
Section: Improving Quality Of Life With Exercise and Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yen and Lin introduced physical activity to older adults in a long-term care facility in Taiwan, showing significant QOL benefits. 107 Lavie and Milani compared older adults ≥70 years of age to younger patients <55 years in CR, finding those ≥70 years had significant improvement in QOL scores, even greater than in younger patients (20% vs 15%, P = .03). 108 Another study by Lavie and Milani showed QOL, pain, energy, physical function, well-being, general health, and mental health scores all significantly improved in cardiac patients who participated in CR, with similar benefits in patients ≥65 years and younger cohorts.…”
Section: Improving Quality Of Life With Exercise and Physical Activitymentioning
confidence: 99%
“…A rich literature demonstrates the links between QOL and physical activity. Yen and Lin introduced physical activity to older adults in a long‐term care facility in Taiwan, showing significant QOL benefits . Lavie and Milani compared older adults ≥70 years of age to younger patients <55 years in CR, finding those ≥70 years had significant improvement in QOL scores, even greater than in younger patients (20% vs 15%, P = .03) .…”
Section: Modifying Frailty With Exercise and Physical Activitymentioning
confidence: 99%
“…An engagement in moderate physical activities is proven to be the key element of achieving a healthy and active lifestyle which is promoted by active aging [4,5]. The benefits of physical activities include the enhancement of body balance, strength, and mental health [6][7][8]. The physical activities discussed in this paper include active activities and passive activities.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have discovered that people's increase in age is inversely proportional to their physical activity levels. It is reported that most seniors globally are inactive [8,21,22]: 45% of Europeans aged around 60 are physically inactive [23]; only 20% of older females and 31% of older males are capable of achieving the 2 h and 30 min moderate physical activities per week suggested by WHO [24]. It is also pointed out that seniors tend to avoid or reduce their frequency of park visits [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation